Implementation of physically active classes and active breaks: An experience report from the Erguer/Aracaju project (Research, Society and Development, 2023)
The Erguer/Aracaju project aims to monitor cognitive evolution and academic performance, as well as the reduction of students' sedentary behavior through movement in class. This experience report aims to analyze the intervention and implementation of Projeto Erguer/Aracaju regarding physically active classes and active breaks. Currently, the research takes place in six schools in the municipal network of Aracaju-SE. Schools are divided into intervention groups (physically active classes and active breaks) and control groups. The sample consists of 181 children in the first year of elementary school in the 2022 school year. This report reflects on the information obtained empirically from data collection, weekly meetings of the research team, field diaries, filming of interventions and teacher training. The project's content was included in the pedagogical organization of the schools during the school year, and the results indicate that the actions of the Erguer/Aracaju were positive and project need to be intensified so that this new perspective remains strengthened.